(3GdGbJUGO GdLRFj (B:s (3GdfXQjGJ h GdSjGSGJ (B/s - (3GdaJdGhj, cGed YdGhjs; (3GdRHjOj, MSf dWja s ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2009)
(3fXQjI Sdhc GdeSJgdc , JhGRf GdeSJgdc , fXQjI GdYQV ,fXQjI GdJhGRf , fXQjI GdGfJGL , fXQjI GdJcGdja , GdGjQGOGJ h GdGQHGM , JhGRf GdefTCI aj GdefGaSI GdcGedI , JhGRf GdefTCI aj Shb GdGMJcGQh aj GdefGaSI GdGMJcGQjI h aj Shb EMJcGQ GdbdI , , GdJhGRf GdYGe h GbJUGO GdQaGgjI (B.s
(3eQGLY U(B.297s
Keywords: (3GdEbJUGOs; (3GdEbJUGO GdLRFjs; (3GdEfJGLs